Environmental Science : a global concern - Cunningham, William P.; Saigo, Barbara Woodworth (Dubuque : Wm. C. Brown Publishers, 1995)
Environment Management
Includes index and bibliographical references
2000-02-14
Keywords: Environmental Protection; Environmental Health